Measuring cash flow and overdraft for fuzzy project networks with overlapping activities. Issue 4 (19th May 2017) - Yu, Min-Chun; Dang, Van-Loi; Yeh, Hui-Chung
Abstract: Overlapping activities with imprecise durations to accelerate schedules has an impact on scheduling a construction project. The project may need to be rescheduled to suit the available overdraft limitation rather than to adopt the least total cost schedule. However, past research has seldom conducted a risk analysis on the project cash flow and overdraft requirements for projects with overlapping activities in a fuzzy environment. This research uses fuzzy DSM-based scheduling and proposes an algorithm to calculate the cash flow and overdraft at different risk levels. A numerical example is illustrated to demonstrate the algorithm's effectiveness.